Semantics theories - Maienborn, Claudia; Heusinger, Klaus von; Portner, Paul (Mouton reader., 2019)
"Now in paperback for the first time since its original publication, the material gathered here is perfect for anyone who needs a detailed and accessible introduction to the important semantic theories. Designed for a wide audience, it will be of great value to linguists, cognitive scientists, philosophers, and computer scientists working on natural language. The book covers theories of lexical semantics, cognitively oriented approaches to semantics, compositional theories of sentence semantics, and discourse semantics. This clear, elegant explanation of the key theories in semantics research is essential reading for anyone working in the area"--